Cost-Effectiveness of Total Colonoscopy in Screening of Colorectal Cancer in Japan. (12th January 2012) - Sekiguchi, Masau; Matsuda, Takahisa; Tamai, Naoto; Sakamoto, Taku; Nakajima, Takeshi; Otake, Yosuke; Kakugawa, Yasuo; Murakami, Yoshitaka; Saito, Yutaka
Abstract : Introduction . In Japan, the cost-effectiveness of total colonoscopy (TCS) for primary screening of colorectal cancer (CRC) is unclear. We compared the cost of identifying a patient with CRC using two primary screening strategies: TCS (strategy 1) and the immunochemical fecal test (FIT) (strategy 2). Materials and Methods . We retrospectively analyzed the TCS screening database at our institution from February 2004 to August 2010 (strategy 1, n = 15, 348 ) and the Japanese nationwide survey of CRC screening in 2008 (strategy 2, n = 5, 267, 443 ). Results . 112 and 6, 838 CRC cases were detected in strategies 1 and 2, costing 2, 124, 000 JPY and 1, 629, 000 JPY, respectively. The rate of earlier-stage CRC was higher in strategy 1. Conclusions . The cost was higher using TCS as a primary screening procedure. However, the difference was not excessive, and considering the increased rate of detecting earlier CRC, the use of TCS as a primary screening tool may be cost-effective.